Criminal Provisions Against Companies that do not Participate in BPJS Employment - Lastarina Br Pakkar; Sanco Simanullang; Habieb Pahlevi (Contemporary Journal of Applied Sciences, 2024)
Companies are required to register their employees with BPJS Ketenagakerjaan to provide social protection mandated by Law Number 24 of 2011. However, many companies fail to comply, prompting the government to impose administrative and criminal sanctions to enhance compliance. This study aims to analyze criminal provisions for companies not registered with BPJS Ketenagakerjaan and their impact on worker protection. Using a normative juridical research method, this study evaluates the effectiveness of Article 55 of the BPJS Law. The findings reveal that companies may face imprisonment of up to 8 years or fines up to IDR 1 billion. However, the implementation of these sanctions is hindered by vague norms, particularly in defining violation criteria and delayed payment durations. This legal uncertainty affects the effectiveness of worker protection. Therefore, regulatory improvements are necessary to enhance legal certainty and the effectiveness of sanction enforcement.